2007
DOI: 10.1016/j.jcat.2006.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of phenol over high-silica beta zeolite: Effect of zeolite acidity and crystal size on catalyst behaviour

Abstract: A systematic investigation has been carried out, aiming at elucidating several aspects of the gas/solid methylation of phenol over high Si/Al ratio BEA-structured zeolite in protonated form. The catalysts have been characterized by several techniques, such as XRD, SEM, BET, ICP, FT-IR, TGA, micro-calorimetry and modelling by ab initio calculations. The correlation between these characteristics and kinetics and mechanistic features of the catalytic reaction, as well as of catalyst deactivation, showed that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 63 publications
2
33
0
Order By: Relevance
“…Formation of heavy dialkylated products, in particular xylenols, may also form carbonaceous products and contribute to catalyst deactivation. Indeed, the retention of polyalkylated phenols has been proposed as one of the mechanism responsible for the progressive deactivation of the catalyst in the methylation of phenol [13]. The observed correlation in Table 3 between X 0 P and d 0 suggests in fact that the catalyst activity decay increases with the formation of heavier secondary products at high conversion levels.…”
Section: Catalyst Deactivationmentioning
confidence: 98%
See 1 more Smart Citation
“…Formation of heavy dialkylated products, in particular xylenols, may also form carbonaceous products and contribute to catalyst deactivation. Indeed, the retention of polyalkylated phenols has been proposed as one of the mechanism responsible for the progressive deactivation of the catalyst in the methylation of phenol [13]. The observed correlation in Table 3 between X 0 P and d 0 suggests in fact that the catalyst activity decay increases with the formation of heavier secondary products at high conversion levels.…”
Section: Catalyst Deactivationmentioning
confidence: 98%
“…Solid bases, in particular MgO, selectively alkylate phenol in ortho-position, producing essentially o-cresol and 2,6 xylenol [5,6]. Solid acids such as silicaalumina, Nafion-H resin, HPA/SiO 2 , and zeolites HBEA and HY, convert phenol to a mixture of anisole, cresols, xylenols and methylanisoles [7][8][9][10][11][12][13]. Brønsted solid acids promote the O-alkylation of phenol [10,11] while Lewis solid acids (SiO 2 -Al 2 O 3 ) and zeolites containing similar amounts of Lewis and Brønsted acid sites (HBEA, HY) favor the C-alkylation of phenol [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work [61] we reported that in the gas-phase methylation of phenol catalyzed by H-BEA zeolites, the main products of methanol transformation were pentamethyl and hexamethylbenzene; the latter, and polynuclear aromatics as well, were responsible for the progressive catalyst deactivation.…”
Section: The Transformation Of Methanol With the Acid Catalystmentioning
confidence: 98%
“…A further increase of temperature led to a decrease of conversion. This can be attributed to two concomitant phenomena, (i) a progressive deactivation of the catalyst, due to the formation of condensed aromatics (coke precursors) by transformation of methanol [61][62][63][64][65][66], and (ii) a considerable increase in the parallel reactions of methanol decomposition to light compounds. Indeed, the spent catalyst was coked, and its surface area was considerably lower than that one of the fresh catalyst ( Table 1).…”
Section: The Methylation Of Phenol With the Acid Catalystmentioning
confidence: 99%
See 1 more Smart Citation